2012
DOI: 10.1111/j.1467-7679.2012.00584.x
|View full text |Cite
|
Sign up to set email alerts
|

Policy Sequencing and the Development of Rice Value Chains in Senegal

Abstract: In response to the world food crisis in 2008, Senegal developed a productivist national food self-sufficiency programme. However, the critical question is not whether the programme can meet its ambitious target of self-sufficiency in rice production by 2015, but, if it does, how will domestic rice reach urban markets, where consumers generally prefer imported rice for its superior grain quality. Information collected through interviews and a stakeholder workshop advances the argument that policy sequencing wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 41 publications
2
46
0
1
Order By: Relevance
“…Similar findings were made in the present study and the same situation applies to other countries in West Africa (Demont and Rizzotto, 2012;Nwanze et al, 2006).…”
Section: Relationship Of Survey With Other Consumer Preference Studiessupporting
confidence: 92%
See 1 more Smart Citation
“…Similar findings were made in the present study and the same situation applies to other countries in West Africa (Demont and Rizzotto, 2012;Nwanze et al, 2006).…”
Section: Relationship Of Survey With Other Consumer Preference Studiessupporting
confidence: 92%
“…First, the farmers would need to work with other stakeholders such research, extension, millers, food technologist, traders and government to acquire the right skills and equipment to make their final product attractive to consumers. In a recent study in Senegal, the authors recommended that, any large scale investment in rice production must be preceded by investments in post-harvest, grain-quality infrastructure to improve the marketability and competitiveness of domestic relative to imported rice in West Africa (Demont and Rizzotto, 2012). Second, government institutions that consume large quantities of rice such schools and prisons could be made to purchase only locally produced rice.…”
Section: Constraints To Rice Cultivationmentioning
confidence: 99%
“…For example, in Senegal, Demont and colleagues reported that the majority of urban consumers are willing to pay quality premiums for local rice [57,58]. A similar situation was found in Benin [59] and Togo [55].…”
Section: Rice Value Chains and Economic Globalizationmentioning
confidence: 78%
“…Demont [31] and Demont and Rizzotto [57] proposed a combination of supply-shifting investment, value-adding, and demand-lifting investment policies as options for achieving a self-sufficient rice supply in SSA. Supply-shifting investments address some of the concerns overlooked by both protectionism and liberalization policies.…”
Section: Development Policies and Vulnerability Of Rice Value Chainsmentioning
confidence: 99%
“…Analogously to Demont and Rizzotto [16], data was collected through mixed methods including literature reviews, focus group discussions (FGDs) with farmers, stacked surveys with different rice value chain stakeholders, and a participatory workshop bringing several value chain actors together. Principles for sustainable rice production as defined by the Sustainable Rice Platform (SRP) [13].…”
Section: Methodsmentioning
confidence: 99%